Age-specific mortality risk of mild diastolic dysfunction among hospitalized patients with preserved ejection fraction. (1st June 2021) - Granot, Yoav; Ben-Assa, Eyal; Sapir, Orly; Laufer-Perl, Michal; Topilsky, Yan; Rozenbaum, Zach
Abstract: Background: The conveyed risk of mild diastolic dysfunction (MDD) according to age had not been thoroughly studied. We aimed to investigate the mortality-risk of MDD by age-groups among inpatients with preserved ejection fraction (EF), and determine ranges of diastolic function parameters by prognosis. Methods: In a single-center retrospective study we identified inpatients who underwent echocardiography between 2012 and 2018 and had preserved EF without significant valvulopathies. Propensity scores were used to adjust for baseline characteristics and main diagnoses at discharge. Comparisons for all-cause mortality between MDD and normal diastolic function were conducted by age groups. Using classification and regression trees (CART) modeling we determined age-specific cut-offs according to outcome. Results: The cohort consisted of 15, 777 inpatients. Mortality rate during a 33.9-months median follow-up was 21.6%. MDD was associated with increased mortality risk among all ages up to 90 years, thereafter no difference was detected. Adjusted hazard ratios inversely related to age – 1.99(95%CI 1.25–3.16, p = 0.004), 1.82(95%CI1.46–2.26, p < 0.001), 1.88(95%CI1.64–2.15, p < 0.001), 1.78(95%CI1.59–2.01, p < 0.001), and 1.32(95%CI0.95–1.83, p = 0.093), for 18–44, 45–59, 60–74, 75–89, and ≥90 years, respectively (Pinteraction = 0.009). New cut-offs of E/e' for ages 75–89(16), e' lateral for ages ≥90(6 cm/s), e' septal for ages 60–74(5 cm/s), and E/A ratio for ages 18–44(1.5), predicted outcome more accurately than guidelines-based recommendations . The remaining cut-offs were not better predictors compared to guidelines-based recommendations. Conclusions: MDD is a consequential finding at all ages up to 90 years among inpatients with preserved EF, although its significance decreases with age. Diastolic function of several age-groups may be better delineated by cut-offs that presage adverse prognoses. Helsinki committee approval number: 0170-17-TLV. Highlights: Prognostic implications of mild diastolic dysfunction (MDD) remain understudied. We studied the mortality risk of MDD among hospitalized patients. MDD was associated with an increased mortality risk among all ages up to 90 years. New age-appropriate cut-off values for MDD derived by outcome were proposed. Certain new values were better prognostic predictors vs the current recommendations.